2011
DOI: 10.1111/j.1365-2702.2010.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Conflict management styles used by nurse managers in the Sultanate of Oman

Abstract: Conflict can affect patient care if handled badly. Poorly handled conflict results in lower staff morale and poorer retention, both adversely affect patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 37 publications
10
53
1
Order By: Relevance
“…19 This style emphasizes quick, mutually acceptable decisions that somehow satisfy both parties. 9 Our study showed that male nurses had higher scores of compromising style than did their female colleagues, which is in line with the results of the studies of Al-Hamdan et al 9 and Chan et al 13 This difference in conflict management approaches among male and female nurses confirms the socializing effects of gender role expectations in Iran. For instance, men are generally expected to develop masculine …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…19 This style emphasizes quick, mutually acceptable decisions that somehow satisfy both parties. 9 Our study showed that male nurses had higher scores of compromising style than did their female colleagues, which is in line with the results of the studies of Al-Hamdan et al 9 and Chan et al 13 This difference in conflict management approaches among male and female nurses confirms the socializing effects of gender role expectations in Iran. For instance, men are generally expected to develop masculine …”
Section: Discussionsupporting
confidence: 93%
“…Assertiveness and cooperation are involved in the collaboration style. 9,11 Those who use accommodating style face conflicts passively and follow the decisions of other parties. They show low concern for themselves and high concern for others and tend to accept the other party's purpose.…”
Section: Conflict As a Natural Results Of Human Communication Ismentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, RNs predominantly use an integrating conflict management style, which can be interpreted as constructive conflict management in that it might indicate awareness of the context. [22,23] As the participants in this study rated their conflict management competence as high, this can be understood as using an integrating conflict management style. This is also confirmed by the fact that RNs who used their expertise in CMC had higher self-reported CMC than those who did not use such competence.…”
Section: Discussionmentioning
confidence: 99%